Upaya meningkatkan kemampuan motorik halus melalui kegiatan menjahit bervariasi dengan berbagai media di PAUD Alquran Az-Zahra Banyurip Alit - M. Rosikhul Ilmi (Perkumpulan Kualitama Edukatika Indonesia, 2021)
Various sewing activities are an appropriate step in improving children's fine motor skills, because they are used to express themselves. To produce interesting stitches really helps develop a child's imagination in improving their fine motor skills. PAUD Al-Quran Az-Zahra Banyurip Alit Pekalongan City on fine motor activities failed in various sewing materials, this can be seen from the work of children with a total of 20 children who got good grades only 5 children, only 4 children, and less than 11 children. The problem is the lack of physical fine motor skills of children in various sewing activities. This is because the media used is less varied so that children feel bored. So we need an active learning method using various media. The aim of this research is to improve children's fine motor skills in sewing with various media. The benefits are expected to contribute to the development of science. In carrying out the improvement of learning through two cycles. The results of observations and research in the second cycle increased more than the previous cycle. The results of the previous comparison had a success rate of only 45%, the first cycle was 65%, the second cycle reached a 95% success rate. So it can be concluded that sewing activities have a positive impact on fine motor development and can improve children's ability to sew with various media.